Information and Digital Literacies : A Curricular Guide for Middle and High School Librarians. - Farmer, Lesley S. J. (Blue Ridge Summit : Rowman & Littlefield Publishers, Incorporated, 2015)
Information and Digital Literacies: A Curricular Guide for Middle and High School Librarians is a practical guide to help school librarians design and deliver effective instruction that addresses the knowledge, skills and dispositions of information and digital literacies. The ready-to-implement curricular guide features instructional design strategies, model middle and high school curriculum, including a scope-and-sequence, stand-alone courses, units of instruction, and sample learning activities, and ties to new AASL and ACRL information literacy standards, ISTE technology standards, 21st Century Partnership framework, and Common Core State Standards.
Implications for School Librarians -- References -- 6 Connecting the Curriculum -- Curriculum Characteristics -- Scope and Sequence -- Curriculum Mapping -- College/Career Readiness -- Articulation -- Collaboration -- Infrastructure -- Middle School Teacher Workshop: Learning About Technology -- Implications for School Librarians -- References -- 7 Model Curriculum for Middle School -- Content -- Sample Learning Activities -- Learning Activity: Budgeting for Now and the Future -- Representative Learning Activities -- Configurations -- Investigating Careers -- Implications for School Librarians -- 8 Model Curriculum for High School -- Content -- Sample Learning Activities -- Learning Activity: Information Cycle Flowchart -- Representative Learning Activities -- Configurations -- I-Search Research Course -- Capstone Course: Community-Based Action Research Project -- Implications for School Librarians -- Bibliography -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Computer literacy - Study and teaching (Secondary) - United States; Electronic books